Pengelolaan Arsip Dinamis Aktif Sma Datuk Batu Hampar Pekanbaru - Ani Muntama; Umar Faruq (Fakultas Tarbiyah dan Keguruan, 2020)
The aim of this research was to examine the management of active and dynamic archives in Senior High School Datuk Batu Hampar Pekanbaru and factors that influenced the management of active and dynamic. As for the problems in this researchwerehow the management of active and dynamic archives wasand what factors that influenced the management of active and dynamic archieves in Senior High School Datuk Batu Hampar Pekanbaru. Techniques used in collecting data were interview, observation, and documentation. Then, data was analyzed by reducing data, presenting data, and drawing conclusion.The research finding revealed that organizing actives and dynamic archives in Senior High School Datuk Batu Hampar PekanbaruThe head of administration dan staff implemented the maintenance in managing active and dynamic archives, implemented the archives storage, instructed the staffs to always take note for every activities, assigned the staffs to do checking for all archieves and destroyed archieves. It was found that the factors which influenced the management of of archieve was the lack of staffs’ understanding about archieves, limited facilities of archieves, authority in using facilities and maintained good communication.